Unraveling the Mysteries of Phospholipid Scrambling - Sims, Peter J.; Wiedmer, Therese (Thrombosis and Haemostasis, 2001)
Plasma membrane phospholipid asymmetry is maintained by an aminophospholipid translocase that transports phosphatidylserine (PS) and phosphatidylethanolamine (PE) from outer to inner membrane leaflet. Cell activation or injury leads to redistribution of all major lipid classes within the plasma membrane, resulting in surface exposure of PS and PE. Cell surface-exposed PS can serve as receptor sites for coagulation enzyme complexes, and contributes to cell clearance by the reticuloendothelial system. The mechanism(s) by which this PL ”scrambling” occurs is poorly understood. A protein called phospholipid scramblase (PLSCR1) has been cloned that exhibits Ca2+-activated PL scrambling activity in vitro. PLSCR1 belongs to a new family of proteins with no apparent homology to other known proteins. PLSCR1 is palmitoylated and contains a potential protein kinase C phosphorylation site. It further contains multiple PxxP and PPxY motifs, representing potential binding motifs for SH3 and WW domains implicated in mediating protein-protein interactions. Although at least two proteins have been shown to associate with PLSCR1, the functional significance of such interaction remains to be elucidated. Evidence that PLSCR1 may serve functions other than its proposed activity as PL scramblase is also presented.
Keywords: Phospholipid; phosphatidylserine; plasma membrane; phospholipid scramblase; phospholipid asymmetry